MARGINAL REGIONS MATHEMATICS TEACHERS’ PERCEPTION OF THE USE OF MANIPULATIVE TOOLS - Krisna Satrio Perbowo; Dian Lestari; Syafika Ulfah; Rosida Rakhmawati (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Manipulative tool is one of the learning media most likely to be used by teachers, including those in marginal regions. This study aimed to determine the perception of mathematics teachers in marginal regions toward using manipulative tools as learning media. This study used surveys designed with two domains: the use of manipulative tools as learning media and the importance of manipulative tools as learning media. The sample for this study comprised 81 teachers who were either currently teaching or had previously taught at the elementary, middle, and high school levels in marginal regions. This study found that the manipulative tools mostly used by mathematics teachers in marginal regions are objects obtained from the surrounding environment (used cans, paperboard, coins, rulers, stones, and sticks). This study revealed that the mathematics teacher's perception of manipulative tools as learning media and the importance of manipulative tools as learning media are generally in the medium category.